The reserve supply channel of unconventional monetary policy - Diamond, William; Jiang, Zhengyang; Ma, Yiming (Journal of Financial Economics, 2024)
We find that central bank reserves injected by QE crowd out bank lending. We estimate a structural model with cross-sectional instrumental variables for deposit and loan demand. Our results are determined by the elasticity of loan demand and the impact of reserve holdings on the cost of supplying loans. The reserves injected by QE raise loan rates by 7.4 basis points, and each dollar of reserves reduces bank lending by 7.7 cents. Our results imply that a large injection of central bank reserves has the unintended consequence of crowding out bank loans because of bank balance sheet costs.